The impact of macroeconomic news on quote adjustments, noise, and informational volatility - Nikolaus Hautsch; Dieter E. Hess; David Veredas (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
We study the impact of the arrival of macroeconomic news on the informational and noise-driven components in high-frequency quote processes and their conditional variances. Bid and ask returns are decomposed into a common ('efficient return') factor and two market-side-specific components capturing market microstructure effects. The corresponding variance components reflect information-driven and noise-induced volatilities. We find that all volatility components reveal distinct dynamics and are positively influenced by news. The proportion of noise-induced variances is highest before announcements and significantly declines thereafter. Moreover, news-affected responses in all volatility components are influenced by order flow imbalances.
Keywords: C32; G14; E44; 330; efficient return; macroeconomic announcements; microstructure noise; informational volatility; Wirtschaftsinformation; Ankündigungseffekt; Börsenkurs; Bid-Ask Spread; Kapitalertrag; Informationseffizienz; Volatilität; Noise Trading; Mikrostrukturanalyse; Theorie; Schätzung; Zinstermingeschäft; Deutschland